Ação de extratos foliares de campomanesia xanthocarpa (mart.) O. Berg sobre a germinação e crescimento inicial de lactuca sativa L. - Silva, Josiele Aparecida (2022)
Plant species from the Brazilian cerrado highlight their pharmacological potential on several fronts. The Campomanesia family demonstrates adequate and genotoxic capacity, especially due to the presence of flavonoids, tannins and saponins. Characterized by its rusticity, its biroba (Xanthocarpa City) for its excellent adaptation to hot climates, poor soils in areas of low rainfall and nutrients. These make urban species suitable for use in afforestation and ecological restoration of degraded areas, as well as for the characteristics of production in the cerrado, where it is widely commercially distributed. Among the various sources from secondary metabolism, there are allelochemicals, which when released into the environment by allelopathic plants, cause interference in the environment. As a substance that interferes with cytogenotoxic activity, it may have the ability to interfere with cytogenotoxic activity. Where a plant releases bioactive metabolites into the environment, direct contracts are contracted not built nearby, generating a selected partnership with the plant. A direct method and target of study to test biological substances, evaluating changes in physiological and morphological parameters in plants. This dissertation is a fortress in chapters, where chapter 1 presents a review of the species and the various developments in the present work. Chapter 2 presents the allelopathic effect of hydroethanolic and aqueous extracts obtained from C. xanthocarpa leaves in bioassays of L. sativa cv. “Babá de Verão”, followed by characterization of the extract with the highest allelopathic effect by means of the ESI-MSn mass spectrometry effect. Both forms of generation had allelopathic action, being greater and more intense in the aqueous extract, with a dependent effect for the parameters of germination and initial growth of lettuce seedlings.